Attitudes toward substance use among females on parole: the effects of relationship quality between parole/probation officers and female offenders - Lawrence, Timothy I. (Psychology, crime & law, 2024)
The relationship between parole/probation officers and female parolees can influence parolees’ successful reentry into the community. Constant and positive contact with parole officers might help parolees avoid problematic behavior. The current study focuses on the reduction in substance use parolees among female parolees as a product of the relationship quality with parole officers. This cross-sectional study used a structural equation model to examine whether relationship quality between parole/probation officers with female parolees predicted attitudes toward substance use avoidance. This study also examined whether criminogenic needs and employment self-efficacy explained the relationship between quality relationships and attitudes toward substance use (N = 226). The results suggest that relationship quality, criminogenic needs, and employment self-efficacy positively related to attitudes toward substance use avoidance. Mediational results suggest that criminogenic needs and employment self-efficacy explained the relationship between relationship quality and female parolees’ attitudes toward substance use. Therefore, establishing a positive relationship with a parole officer might help reduce female parolees’ substance use by increasing employment attitudes and reducing temptations to engage in criminal behavior.